Modelling return on marketing in the South African banking sector - Mabuzane, Belinda K. (My University, 2012)
In today‟s increasingly dynamic and competitive markets, organizations are continuously pressurized to meet financial targets in order to realise company goals in an efficient and effective manner. The banking sector in South Africa has, for a very long time, operated in a predominantly oligopoly market, however, due to increasing pressure from new entrants like Capitec Bank, there has been a shift of focus to ensuring long term profitability and competitiveness as the new entrants are constantly implementing strategies that cause customer switching. The literature reveals that long-term profitability requires that a firm implements sustainable development projects to ensure long-term profitability. However, many of the profitability models in use today do not have a variable for sustainable development and yet it is a key factor in drawing returns on investment. This study adopts the South African banking sector and investigates the applicability of Rust, Lemon and Zeithaml‟s (2004) return on investment model for the various initiatives that the banks have implemented. From qualitative research with the banks, it was found that sustainable development forms a large part of the annual budget with the aim of improving the brand perceptions and increasing the likelihood of customer retention and attraction. However, the results from the bank‟s customers reveal that the initiatives being sponsored by the banks have very little effect on their decision to switch or remain banking with a specified bank. Basic customer satisfaction techniques like clear communication and customer care still outweigh any corporate initiative like sponsoring the local soccer league thus although these initiatives do benefit to keep the brand name in customer‟s minds, they do less in realising returns. The model reveals a technique to quantify return on investment taking into account factors like sustainable development and it was found that the model is applicable and useful in a South African setting. Recommendations include applying the model to gauge not only the possibility of returns but also how much a company can expect to receive after investing a specified amount of money on any initiative. This model will be very useful for planning especially for capital intensive projects as the current economic environment cannot accommodate for misappropriation of funds.
Thesis (M.Com. (Marketing Management and Information Systems))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic and Business Sciences, 2012.
Keywords: Bank marketing--South Africa; Banks and banking--Customer relations--South Africa; Finance--Mathematical models; Rate of return--Measurement